Strategic human resource leader : how to prepare your organization for the six key trends shaping the future - Rothwell, William J. (Davies - Black Pub. Palo AltoUS, 1998)
Identifies and discusses key business trends which will significantly influence organizations in the 21st century. Includes topics such as: changing technology; continuing cost containment; and, the growing importance of knowledge capital. Presents the human resource (HR) practitioner as the change leader. Suggests how to identify and set priorities for the HR function; and translate strategy into action. Proposes ideas for defining and measuring HR results. Reviews the roles and competencies which HR personnel need to adopt and acquire respectively, in order to perform effectively in organizations of the future.